Clinical practice guideline for diagnosis and treatment of Hemophilia in the Peruvian Social Security (EsSalud) - Herrera-Cunti, Celina (2021)
Background: This article summarizes the clinical practice guide (CPG) for diagnosis and treatment of hemophilia in the Social Security of Peru (EsSalud). Objective: To provide evidence-based clinical recommendations for the diagnosis and treatment of hemophilia in EsSalud. Material and Methods: A guideline development group (GDG) was formed, which included specialist physicians and methodologists, who formulated clinical questions. Systematic searches of systematic reviews were conducted and - when deemed relevant - primary studies in PubMed during 2020 and 2021. Evidence was selected to answer each of the proposed clinical questions. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic working meetings, the GEG used the GRADE methodology to review the evidence and formulate recommendations. The CPG was reviewed by external experts before its approval. Results: The CPG addressed 09 clinical questions, divided into 02 topics: diagnosis and treatment. Based on these questions, 05 recommendations were formulated (01 strong and 04 conditional), 51 points of good clinical practice, and 02 flow charts. Conclusion: Evidence-based recommendations were issued for the diagnosis and treatment of persons with hemophilia.